OP0037 Fibrinolytic system and ace i/d polymorphism in systemic sclerosis. (1st June 2001) - Angotti, C; Gensini, F; Fatini, C; Battaglini, B; Sticchi, E; Fedi, S; Righi, A; Pepe, G; Abbate, R; Cerinic, M Matucci
Abstract : Background: In Systemic sclerosis (SSc), an imbalance of the fibrinolytic system was shown. In vivo and in vitro studies suggest a role for Renin Angiotensin System in the regulation of fibrinolytic balance: Angiotensin II (Ang II) increases the plasminogen activator inhibitor?1 (PAI-1) production and secretion, and ACE reduces t-PA production. A polymorphism in the ACE gene consisting of an insertion or deletion (I/D) of 287 bp fragment in intron 16 was described. The D allele of ID polymorphism is associated with an increased level of ACE and ACE gene polymorphism may influence the production of Ang II. Objectives: To investigate possible alterations in the fibrinolytic system and to examine the role of ACE I/D polymorphism in SSc. Methods: PAI-1 activity, t-PA and D-Dimer plasma levels were measured in 61 SSc patients (36 limited, 25 diffuse) and 108 healthy controls. ACE I/D polymorphism was genotyped by PCR. PAI-1 activity and t-PA levels were assayed by chromogenic method and D-Dimer levels by ELISA. Results: A significant difference in ACE genotype distribution (chi2 = 9.79 p = 0.007) and allele frequency was observed between patients and controls (0.64 vs 0.50 p = 0.009). In limited SSc a higher frequency of ACE D allele was found (0.68 vs 0.56 in diffuse SSc p = 0.23). By univariate analysis an association between ACE D allele and limited, but not diffuse SSc, was found (OR DD+ID/II = 6.44 95% CI 1.45–28.54 p = 0.005 and OR DD+ID/II = 1.91 95% CI 0.60–6.08 p = 0.31 respectively). Median values of PAI-1, t-PA and D-Dimer were 6.2 U/ml (range 1–37.5), 10.5 ng/mL (range 4.3–28.1) and 156 ng/mL (range 64–1064, respectively. Patients had higher t-PA and D-Dimer mean levels than controls (p = 0.000001 and p = 0.02, respectively). No difference was observed in PAI-1 plasma levels between patients and controls (p = 0.85). No association between high PAI-1, t-PA and D-Dimer plasma levels and ACE D allele was observed. Conclusion: These data suggest that ACE D allele is highly associated with limited SSc. Thus, we could hypothesise that this allele may represent a risk factor for the development of limited SSc. Other mechanisms than the alterations of fibrinolytic system may have a role in determining the microvascular damage.